MANUFACTURING OF THINGS AND CHARACTERISTICS OF CHILLI, ORANGE SKIN, AND CINNAMON EXTRACT USING MACERATION METHOD - Dwi Mulyana Salsabila Baladraf; Yustika Yusuf; Agusrianto Yusuf (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This study aims to identify the chemical compounds in the extracts of cinnamon, orange and chili by maceration method. The maceration method is a method of extracting the juice from simplicia by immersing the simplicia in a liquid extract at a temperature usually 15-25°C. Maceration is also a preliminary process for percolation manufacturing. The method used is the experimental method. The results showed that in the making of the tincture in this study, including the original tincture, Original Tincture is a tincture made by maceration or percolation. Example: Macerated tincture; Opii Tinctura, Valerianae Tinctura, Capsici Tinctura, Myrrhae Tinctura, Opii Aromatica Tinctura, Polygalae Tinctura. Tinctures made by percolation, for example: Belladonae Tinctura, Cinnamomi Tinctura, Digitalis Tinctura, Lobeliae Tinctura, Strychnini Tinctura, Ipecacuanhae Tinctura, because based on the method of manufacture, namely by maceration.